An ISM approach for modelling the enablers of sustainability in market-oriented firms. (2017) - Agrawal, Amit Kumar; Kumar, Divesh; Rahman, Zillur
Rising environmental concerns and the need for preserving resources for future generations have forced market oriented organisations to integrate sustainability into their strategies. The article aims to explore and prioritise those enablers which are essential for incorporating sustainability into market orientated firms. This study posits that integration of sustainability can help market oriented firms achieve a competitive advantage in the long run. Investigation of literature was done and discussions with experts were carried out to identify, select, and retain key enablers. ISM and MICMAC analyses were carried out to identify and classify key market oriented sustainability enablers that could create a competitive advantage for firms based on their direct and indirect relationships with each other. Legislation and pressure from civil society are the most critical enablers of sustainability in a market oriented firm. Researchers can further explore the generalisability of sustainability enablers identified in this study, across various industry.